Non-destructive measurement of chloride ions concentration in concrete – A comparative analysis of limitations and prospects. (20th June 2018) - Abbas, Yawar; Pargar, Farhad; Koleva, Dessi A.; van Breugel, Klaas; Olthuis, Wouter; van den Berg, Albert
Highlights: Measuring chloride is crucial for service life assessment of concrete structures. Measurement techniques mainly based on electrochemistry and electromagnetics. Based on the level of assessment different techniques have pro and cons. For existing structure assessment varies from visual to detailed lab investigation. Electrochemical sensor are suitable for installation in new structures. Abstract: In this work, the different techniques for non-destructive in situ measurement of chloride ion concentration are presented. Non-destructive (ND) in situ measurement is crucial for reliable and continuous determination of chloride ion concentration in concrete. Over the last 20 years, several studies have been performed on ND measurements. These were mainly focused on the application of electrochemical and electromagnetic techniques. Each technique has its advantages and disadvantages. Depending on the requirement of assets managers and constructors and considering the limitations, these techniques can be well applied. The main concepts and comparative analysis, in view of possibilities and limitations, of these non-destructive techniques are presented in this paper.